Pertumbuhan Tanaman Tebu Hasil Mutasi Pada Ketinggian Lokasi Berbeda - Abdul Jalil; Sri Hartatik; Sholeh Avivi (Jurnal Biologi Papua, 2022)
The availability of superior sugarcane varieties is one of the causes of the low national sugarcane production. The results of mutations from Bululawang sugarcane (BL) variety obtained three genotypes that have the potential to have high yields. Sugarcane plants can be cultivated in all locations because sugarcane can be grown in tropical and subtropical areas with the main problem of water availability being either shortage (drought) or excess (poor drainage). Increases and differences in sugarcane yields can be caused by fertilization, good water distribution throughout the sugarcane growth cycle, crop management, climate and different varieties. if the plant does not experience a lack of water, its production can reach 123 ton/ha/year, but if the plant is under moderate stress (4-5 weeks without rain) then the production will drop to 108 Ton/ha/year. Therefore, it is necessary to conduct a study to determine the potential of each mutant sugarcane at different locations. This research uses direct observation method to each location. Then the data obtained was analyzed descriptively analytically to provide an overview of the object under study through the data that has been collected as it is without analyzing and making conclusions that apply to the public. The results of the research that the M1 mutant sugarcane had the age of emergence of tillers, the highest number of tillers and was able to adapt very well at an altitude of ± 512 meters above sea level. The M1 mutant sugarcane has the highest plant height, the highest number of segments and is able to adapt very well at an altitude of ±62 meters above sea level. The M2 mutant sugarcane has the highest internode length and is able to adapt very well at an altitude of ±62 meters above sea level. Sugarcane M3 has the stem diameter, the highest internode length and is able to adapt very well to an altitude of ± 512 m asl.Key words: sugarcane; production; mutation; different varieties